Printed triple‐band circularly polarised antenna for wireless systems. Issue 23 (1st November 2014) - Bao, X.L.; Ammann, M.J.
Abstract : A triple‐band circularly polarised microstrip patch antenna operating in the 2.4, 3.5 and 5.7 GHz bands is presented. The antenna consists of two substrate layers with an electromagnetically coupled low‐band patch in the middle layer and a probe‐fed dual‐band patch on the top layer. The impedance bandwidths (voltage standing wave ratio (VSWR) < 2.5) for the three frequency bands are 112, 118 and 427 MHz with 3 dB axial‐ratio bandwidths of 15, 44 and 36 MHz, respectively. The peak gains across the operating bands are 4.2, 5.5 and 4 dBic, respectively.